STRATEGI GURU DALAM MENUMBUHKAN GROWTH MINDSET PADA SISWA SEKOLAH DASAR - Nur Alif Malik, Abdillah; Aldia Sundara, Fazar; Sufyan Tsauri, Ade; Acesta, Arrofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of a growth mindset has become an essential aspect of elementary education, as it encourages students to believe that intelligence and abilities can be developed through effort, perseverance, and continuous learning. However, learning practices in schools remain largely focused on academic achievement rather than the learning process, limiting students' motivation and resilience in overcoming challenges. This study aims to examine teachers' strategies for fostering a growth mindset among elementary school students through a review of relevant literature. The study employed a literature review method by analyzing and synthesizing theories and findings from previous studies on growth mindset, the characteristics of elementary school students, teachers' instructional strategies, and the implementation of growth mindset in the learning process. The findings indicate that teachers play a crucial role in fostering a growth mindset by providing process-oriented praise, constructive feedback, encouraging students to view mistakes as learning opportunities, offering challenges that match students' abilities, using positive and motivating language, creating a supportive learning environment, and promoting self-reflection. These strategies are aligned with the student-centered learning approach advocated in the Merdeka Curriculum and contribute to improving students' learning motivation, self-confidence, perseverance, and academic resilience. Therefore, the consistent implementation of appropriate instructional strategies can effectively support the development of resilient, adaptive, and lifelong learners who are well prepared to face future academic and real-life challenges.